P0462HEMODIALYSIS PREDICTORS IN ANCA-ASSOCIATED VASCULITIS AND ANTI-GLOMERULAR BASEMENT MEMBRANE DISEASE. (6th June 2020) - Menezes, Maria Do Mar; Cardoso, Filipa; Bigotte Vieira, Miguel; Viana, Helena; Góis, Mário; Nolasco, Fernando
Abstract: Background and Aims: Antineutrophil cytoplasmic antibody-associated vasculitis (AAV) and anti-glomerular basement membrane (GBM) disease are autoimmune diseases frequently associated with poor renal outcomes namely hemodialysis. Therefore, the aim of this study was to identify predictors of renal replacement therapy (RRT) at six months in patients with ANCA-associated vasculitis and/or anti-glomerular basement membrane disease. Method: We performed a single center observational, retrospective study in 40 patients with ANCA-associated vasculitis and/or anti-GBM disease diagnosed between January 2013 and June 2019. Clinical, analytical and histological variables were included as well as therapeutic regimens and outcomes. The primary endpoint was renal replacement therapy (RRT) at six months. Continuous variables were presented as means or medians, according to normality and categorical variables presented as frequencies. The comparison between subgroups of patients was performed using the Wilcoxon, Fisher exact test or t-test, chi-square test, according to normality. Univariate logistic regression model was fitted to identify variables associated with renal replacement therapy. STATA 14.2 statistical package was used and p <0.05 was considered statistically significant. Results: We identified 40 patients, with a mean age of 69 years-old, 18 (45%) were male, 37 (95%) Caucasian. Twenty-seven (68%) had hypertension and 3 (8%) diabetes. The majority (33, 83%) presented with constitutional symptoms. Pulmonary manifestations were seen in 12 (30%) and gastrointestinal in 5 patients (12%). The other symptoms were rare. The mean systolic blood pressure was 140 mmHg and mean diastolic blood pressure 73 mmHg. The mean hemoglobin in hospital stay was 9, 4g/dL, albumin 3.0 mg/dL, erythrocyte sedimentation rate 77mm/h, C3 1, 11 UQ, C4 0, 30 UQ, proteinuria 1, 42 gr/24h, hematuria 279 erythrocytes, serum creatinine 3, 4 mg/dL, eGFR 14 ml/min/m2, uric acid 7.1 mg/dL. The average ANCA MPO titles were 382 UQ/L, PR3 751UQ/L and GBM 883UQ/L. During hospital stay 11 patients (28%) needed dialysis. Renal biopsy showed interstitial fibrosis and tubular atrophy grade 0 in 5 patients (13%), grade 1 in 13(33%), grade 2 in 8 (20%) and grade 3 in 14 (35%). The majority had no vessel involvement 24 (60%). Acute tubular necrosis was absent in 13 (33%) patients, grade 1 in 9 (23%) and grade 2 in 18 (45%). Inflammatory infiltrate was present in 25 patients (63%). Regarding treatment, 38 (95%) of patients received pulse methylprednisolone and all prednisolone. Rituximab was administered to 15 (38%) patients and Cyclophosphamide to 14 (35%). Eighteen (45%) received azathioprine and 3 (8%) mycophenolate mofetil. Plasmapheresis was performed in 14 patients (35%). The average time from beginning of symptoms to treatment initiation was 119 days. The mean follow-up was 1094 days. At discharge the mean serum creatinine was 2, 5 mg/dL, eGFR 23ml/min/m 2 and none of the patients died. At six months, mean serum creatinine was 1.6 mg/dL, eGFR 31ml/min/m2 but 15 (38%) patients were dialysis-dependent. Two relapses occurred and 17 (43%) had infections during this period. Five (13%) patients died. At 12 months, mean serum creatinine was 2.0 mg/dL, eGFR 29 ml/min/m2 and (9) 23% patients were dialysis dependent. Six (30%) patients had infections and 5 (13%) died. In the end of follow up 13 (33%) patients had died. On univariate analysis, hemoglobin (OR 0.59 [0.36-0.95], p = 0.031), uric acid (OR 1.85 [1.12-3.05], p = 0.027), hematuria (OR 1.00 [1.00-1.00], p = 0.013), hemodialysis performed during 1 st hospital stay (OR 22.9 [2.3-217.9], p = 0.006) and plasmapheresis ( OR 12.0 [2.4-61.0], p = 0.003) were associated with RRT at six months. Conclusion: RRT in AAV and anti-GBM disease has decreased over the last decades with the use of immunosuppressive therapies. Clinical presentation and plasmapheresis seem the major predictors for RRT.